1991
DOI: 10.1073/pnas.88.20.9161
|View full text |Cite
|
Sign up to set email alerts
|

Preferential T-cell receptor beta-chain variable gene use in myelin basic protein-reactive T-cell clones from patients with multiple sclerosis.

Abstract: Multiple sclerosis is an autoimmune disease in which T lymphocytes reactive to myelin basic protein (BP) could play a central role. T cells specific for BP were cloned from the blood of multiple sclerosis patients and normal individuals, and expression of T-cel receptor variable region genes was analyzed. A remarkable bias for use of f-chain variable region (VP) 5.2 and, to a lesser extent, Vj36.1 was seen among BP-specific clones from patients but not from controls. Multiple sclerosis (MS) is an immune-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(108 citation statements)
references
References 34 publications
(35 reference statements)
3
104
0
Order By: Relevance
“…Uematsu et al (15) analyzed the Va and V13 repertoire in the synovial fluid of an RA patient using inverse PCR, and found that both the Va and V13 repertoires were highly heterogenous and polyclonal, but V132.1 and V133.1 were enriched. In brain biopsy specimens from patients with multiple sclerosis, ValO, V135.2, and V136.1 genes were dominantly expressed (18,19).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Uematsu et al (15) analyzed the Va and V13 repertoire in the synovial fluid of an RA patient using inverse PCR, and found that both the Va and V13 repertoires were highly heterogenous and polyclonal, but V132.1 and V133.1 were enriched. In brain biopsy specimens from patients with multiple sclerosis, ValO, V135.2, and V136.1 genes were dominantly expressed (18,19).…”
Section: Discussionmentioning
confidence: 96%
“…The TCR repertoire in human autoimmune diseases has been analyzed using PCR (15)(16)(17)(18)(19). Palliard et al (16) examined the TCR V13 repertoire in synovial fluid from RA patients and found that the frequency of Vf314-positive T cells was significantly higher in synovial fluid from affected joints than in peripheral blood lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the myelin basic proteinprimed effector CD4 ϩ T cells that mediate experimental allergic encephalomyelitis in H-2 u mice, for example, use V␤8.2 (85). In contrast, there is restricted V␤5.2/V␤6.1 usage by myelin basic protein-specific T cells of multiple sclerosis patients (81). In addition, T cell clones derived from the CNS from multiple sclerosis patients preferentially express V␤6 and produce large amounts of proinflammatory cytokines (82).…”
Section: Discussionmentioning
confidence: 99%
“…Although the DRBl * 1501 haplotype is associated with the highest relative risk of MS, other HLA class II alleles are overrepresented among certain ethnic groups of MS patients: DR4 in Southern Italians ( 15) and Arabs (16) and DR1 3 in Japanese (17) and Mexicans ( 18). In contrast to the well-established association between HLA genes and MS, the association ofTCR genes, either in the germline ( 19,20) or in the hMBP-specific peripheral T cell repertoire (21)(22)(23)(24)(25), with MS is still unclear.…”
Section: Introductionmentioning
confidence: 90%